A MODELING DESIGN BASED ON PSO AND PID IN REDUCTION RIPPLE TORQUE AND RIPPLE FLUX IN MOTOR - Septian Prasyahna; Solly Aryza; Siti Anisah (Sean Institute, 2022)
Direct torque control(DTC) of the induction motor is inclined to a specified value of torque. The torque provided is a speed output regulator, therefore it is mandatory to continue tuning to adjust the Kp, Ki parameters. In conventional proportional-integral (PI) speed controllers, motor performance may differ over time which may lead to torque disturbance uncertainty, causing sluggishness of the flux response so the choice of PID parameters is important for DTC systems. In this paper we present a control technique using Particle Swarm Optimization (PSO) to improve the parameters (Kp, Ki) of the speed controller to reduce torque ripple, stator flux distortion ripple and fast response of rotor speed. Unlike conventional designs, this method is capable of achieving the desired control performance. The closed-loop speed control in DTC for induction motors uses the PSO technique thus providing a practical level of accuracy. The results show good features and strong exemplary in dynamic system response and reduction in motor torque and transients.